Fiscal sustainability and policy interactions - Francesco Bianchi; Giovanni Callegari; Ermal Hitaj; Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2024)
We build a model to study the interaction between default risk, policy changes, and financial frictions within a monetary union. The model features a centralised central bank and decentralised fiscal authorities. Countries have different reputations for fiscal stability, modelled as different probabilities of moving to a Default regime. Borrowing costs for the fiscal authority and firms are affected by the possibility of default. This creates a feedback effect between debt accumulation, reputation, and the depth of a recession following adverse shocks. In this context, we discuss the benefits and limitations of a coordinated monetary and fiscal policy response that removes the risk of default. Adverse energy shocks generate more benign outcomes if accommodated, while a fiscal crisis leads to a vicious circle of debt accumulation, recession, and inflationary pressure. In this case, default and inflation risks can reinforce each other.
Keywords: E50; E62; E30; 330; Euro Area; default; fiscal policy; inflation; large public debt; financial frictions